Fatal infectious mononucleosis in a family - Sanal, Özden; Kale, Gülsev; Ersoy, Fügen; Göğüş, Safiye; Coşkun, Yavuz; Çağlar, Melda; Berkel, A. İzzet (The Turkish Journal of Pediatrics, 1990)
Two male siblings, one aged five and a half months (SB), and the other aged six months (VB), with fatal infectious mononucleosis phenotype of the X-linked lymphoproliferative syndrome, which resulted in the death of both infants, are presented. Both patients had been healthy, one until the age of five and a half months, and the other until the age of six months. Then, they developed a maculopapular rash, hepatosplenomegaly and lymphadenopathy. In one sibling, the serum IgG level was low, the IgM and IgA levels were high, and the proportion of E-rosette forming cells (E-RFC) and in vitro proliferative response to PHA were normal. In the other sibling, however, the serum IgG level was normal, the IgM and IgA levels were high and the stimulation index for proliferative response to PHA was reduced due to increased spontaneous blastogenesis. Anti-EBV antibodies were negative in both siblings, except for the IgM anti-VCA in V.B. A lymph node specimen could be studied in one infant and was found to be positive for the EBV genome. Postmortem histopathological findings included the absence of cortico-medullary differentiation and identifiable Hassal's corpuscles in the thymus and depletion of T-dependent regions of lymph nodes and spleen in V.B. Atypical mononuclear cell infiltration was detected in the portal areas of the postmortem liver biopsy in S.B.
Keywords: fatal infectious mononucleosis; X-linked lymphoproliferative syndrome; thymic pathology